Neural substrates of cognitive biases during probabilistic inference - Alireza Soltani; Peyman Khorsand; Clara Guo; Shiva Farashahi; Janet Liu (Nature Communications, 2016)
Humans are often biased in estimating the precise influence of probabilistic events on their decisions. Here, Khorsand and colleagues report a behavioural task that produces these biases in inference and describe a biophysically-plausible model that captures these behavioural deviations from optimal decision making.